Canine Rise Method: A Conservative Approach for Worn Teeth Rehabilitation with Different Adhesive Restorative Materials - Hamid Kermanshah; Aws Alzwghaibi; Maitham Al-Tufaili; Sholeh Ghabraei (Case Reports in Dentistry)
Background. In this article, two cases with generalized dental wear and four cases with localized dental wear are reported. In some of the cases, the worn teeth were restored with direct composite techniques with no mock-up and articulator mounting according to the canine rise method. This method is used without any change in the intercuspation of posterior teeth without a muscle relaxation appliance. It introduces a stable occlusal condition that can alter neuromuscular reflex activity, leading to improvements in certain muscle pain disorders. It is also used to protect the teeth and supporting structures from abnormal forces that might create a further breakdown and/or tooth wear. Methods. The first step of treatment in all the cases was a composite build-up for maxillary and mandibular canines to restrict and guide the horizontal and vertical jaw movements and create adequate space for restorations. The second step was the placement of direct or indirect restorations on upper and lower anterior teeth efficiently and accurately. Results. This method enhanced the esthetic outcomes in a conservative approach with no reduction in tooth material or time-consuming treatments. Conclusions. This technique can be suggested for the treatment of worn teeth in patients with Angle’s Cl I and Cl II classifications of malocclusion based on the follow-up results. It is not applicable for the treatment of worn teeth in patients with Angle’s class III because occlusion is reversed, and canine teeth do not have guidance role. Practical Implications. This method significantly reduces the overall treatment time, and additional steps are required to restore the worn-out teeth and/or occlusion using the canine rise method.